Implementation of Creative Packaging Concepts for Coffee Products: Findings from a Community Service Program at Elmindi Farm - Rizki Ardiansyah Rubini; Bambang Sukajie; Ria Yuli Angliawati; Nur Syafira Ramona (Borneo Research and Education Center, 2026)
Packaging plays a crucial role in enhancing the attractiveness and selling value of a product, particularly in the coffee industry, which prioritizes quality and local identity. This study aims to examine how Elmindi Farm coffee product packaging influences consumer perceptions and contributes to the marketing strategies of UMKM in Legok Harendong Village, Bandung Regency. This area is known for its Arabica and Robusta coffee commodities. The research was conducted using a descriptive-qualitative approach through direct observation and interviews with business owners and consumers. The study results indicate that visual packaging elements such as design, color, and environmentally friendly materials positively impact brand image. Furthermore, clear product information and local narratives on the packaging contribute to building consumer trust and emotional engagement. Packaging serves not only as a protective product but also as an effective communication and branding medium for expanding the market and increasing the competitiveness of local coffee in the digital era.